2007
DOI: 10.1111/j.1600-0579.2007.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Video‐Assisted Clinical Instruction in Dentistry (VACID) enhances real‐time visualisation of clinical procedures

Abstract: The implementation of VACID in the clinical setting enhances real-time visualisation of surgical procedures beyond what is offered by the conventional observational format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
1
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 11 publications
1
37
1
2
Order By: Relevance
“…Based on mean post-test percentage scores, students performed better after viewing the live lecture as opposed to a video instruction. This is in contradiction to the findings of four other studies in dentistry, which reported favourable outcomes for video in clinical instruction (21)(22)(23)(24). Of these studies, only one conducted a randomised controlled study, whilst two of the studies looked at video as a supplement to conventional lecture.…”
Section: Discussioncontrasting
confidence: 99%
“…Based on mean post-test percentage scores, students performed better after viewing the live lecture as opposed to a video instruction. This is in contradiction to the findings of four other studies in dentistry, which reported favourable outcomes for video in clinical instruction (21)(22)(23)(24). Of these studies, only one conducted a randomised controlled study, whilst two of the studies looked at video as a supplement to conventional lecture.…”
Section: Discussioncontrasting
confidence: 99%
“…This approach allows students to visualise clinical procedures in fine detail and is more conducive to keeping them engaged in the work in progress. An ongoing survey conducted at our institution has been examining the students’ preference to observing surgical procedures with and without the use of VACID (9). Preliminary results have shown that the implementation of VACID in the clinical setting greatly improves the students’ learning experience, interest and satisfaction.…”
Section: The Objectives Of Vacidmentioning
confidence: 99%
“…23 In a study conducted by Bloomfield and Jones, nursing students' experience with using multimedia resources was positive, and they found it to be valuable in the acquisition of clinical skills. [25][26][27][28][29][30] Fakhry and Dehkordi-Vakil, for example, reported that video in a clinical setting improved students' experience, interest, and satisfaction and that, in considering video as a form of educational technology, students appreciated the ability to view and reinforce content. Another study in nursing education found students felt motivated to learn from instructional videos and believed the videos helped them prepare for the skills practice.…”
mentioning
confidence: 99%
“…16 Participants in their study also liked the flexible access to the multimedia resources and the opportunity it provided for independent learning in a time and place of their choice. 29 Evidence of students' perceptions about the use of instrumentation videos in dental hygiene education is lacking. 18 The use of instructional multimedia to teach psychomotor skills has also been explored in physical therapy education.…”
mentioning
confidence: 99%